Characteristics of preblended pork during cooler storage - Curtis L Kastner; Y I Choi; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1987)
Five pork carcasses were used to determine the effects of hot boning and various combinations of salt (0, 1.5, or 3.0%) and a phosphate mixture (0 or 0.5%) on bacteria, TBA (measure of fat rancidity), and pH values of preblended pork (preblends). In both HB (hot boned within 2 hr postmortem) and CB (conventionally boned at 24 hr postmortem) preblends, salt increased (P<.05) TBA values (indicates increased rancidity) and decreased (P<.05) growth of psychrotrophic bacteria, whereas phosphate increased (P<.05) pH and decreased TBA values. Salt levels could be reduced from 3.0 to 1.5% in preblends without storage problems, if phosphate (0.5%) was included. Phosphate (mixture pH 7.2) had little influence on microbial growth of preblends during cooler storage.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Preblended pork; Cooler storage